Extra! Extra! Newspaper framing of the Northern Illinois University shooting: re-conceptualizing contextual framing analysis - Jungdahl, Shauna (My University, 2017)
Research in framing theory has routinely analyzed how different types of newspapers frame an event differently. Research has focused on two different characteristics of the newspapers that cover issues. Some have examined the proximity (nearby or distant) of a paper to the event being framed, while others have examined how newspapers with different market scopes have framed an event differently. Through this research, newspapers have been defined as either being Local or National. However, definitions for this Local and National dichotomy have not been consistent. This study will re-conceptualize the idea of different types of newspapers using a two-dimensional concept that combines proximity and market scope. It will then test the viability of this new concept by comparing different types of newspapers framing of the Northern Illinois University shooting. A content analysis was conducted on newspaper coverage of the shooting using Chyi and McCombs’ (2004) Two-Dimensional Measurement Scheme to determine how stories were framed by various newspapers. Results support this study’s prediction that difference in newspaper framing extends far outside the Local and National categories, and further argues that more comprehensive conceptualizations of types of newspapers must be taken into consideration when conducting a comparison measurement in framing analysis.
This file was last viewed in Adobe Reader DC.
Keywords: Frames (Sociology); Newspapers; Mass shootings--Illinois; Northern Illinois University